Implementasi Metode Pembiasaan dan Keteladanan dalam Pembentukan Karakter Religius Anak - Prastyo, Yudy; Budiwan, Jauhan; Rohman, M. Asvin Abdur (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine the implementation of habituation and role-modeling methods in shaping the religious character of students at Madrasah Ibtidaiyah Mambaul Huda, Panggung Barat, Magetan. The research focuses on three main objectives: describing the implementation of habituation methods, explaining the application of role-modeling practices, and identifying supporting and inhibiting factors in the formation of students’ religious character. This study employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving the principal, Islamic education teachers, and students as research participants. Data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that the habituation method is systematically implemented through daily religious activities such as Qur’an recitation, congregational prayers, memorization of short surahs and Asmaul Husna, as well as weekly and incidental religious programs including istighosah, tahlil, and Islamic holy day commemorations. These activities foster consistent religious behavior among students. Furthermore, the role-modeling method is applied through both intentional and unintentional examples demonstrated by teachers in worship practices, discipline, manners, and moral conduct. Teachers serve as concrete role models, supported by character control books and routine supervision by the madrasah. Supporting factors include strong commitment from school leadership and teachers, a religious school culture, structured programs, and a supportive environment. Meanwhile, inhibiting factors include diverse student backgrounds and limited facilities and human resources. Overall, the habituation and role-modeling methods are implemented comprehensively and sustainably in developing students’ religious character.